Functional sugar-based polymers and nanostructures comprised of degradable poly(d-glucose carbonate)s. Issue 10 (16th February 2017) - Su, Lu; Khan, Sarosh; Fan, Jingwei; Lin, Yen-Nan; Wang, Hai; Gustafson, Tiffany P.; Zhang, Fuwu; Wooley, Karen L.
Abstract : This paper presents the synthesis and aqueous solution-state assembly of functional degradable poly(d -glucose carbonate)s, derived from renewable sources, with practical utility in biomedical applications. Abstract : Fundamental synthetic methodology was advanced to allow for the preparation of a reactive glucose-based block copolycarbonate, which was conveniently transformed into a series of amphiphilic block copolymers that underwent aqueous assembly into functional nanoparticle morphologies having practical utility in biomedical and other applications. Two degradabled -glucose carbonate monomers, with one carrying alkyne functionality, were designed and synthesized to access well-defined block polycarbonates ( Đ < 1.1) via sequential organocatalytic ring opening polymerizations (ROPs). Kinetic studies of the organocatalyzed sequential ROPs showed a linear relationship between the monomer conversion and the polymer molecular weight, which indicated the controlled fashion during each polymerization. The pendant alkyne groups underwent two classic click reactions, copper-catalyzed azide–alkyne dipolar cycloaddition (CuAAC) and thiol–yne addition reactions, which were employed to render hydrophilicity for the alkyne-containing block and to provide a variety of amphiphilic diblock poly(d -glucose carbonate)s (PGCs). The resulting amphiphilic PGCs were further assembled into a family of nanostructures with different sizes, morphologies, surface charges and functionalities. These non-ionic and anionic nanoparticles showed low cytotoxicity in RAW 264.7 mouse macrophage cells and MC3T3 healthy mouse osteoblast precursor cells, while the cationic nanoparticles exhibited significantly higher IC50 (162 μg mL −1 in RAW 264.7; 199 μg mL −1 in MC3T3) compared to the commercially available cationic lipid-based formulation, Lipofectamine (IC50 = 31 μg mL −1 ), making these nanomaterials of interest for biomedical applications.